Argentina : Second Review Under the Stand-By Arrangement and Request for Waivers of Nonobservance and Applicability of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2003)
Sound macroeconomic policies are key to improving market sentiment and smoothing the political transition. Implementation of structural reforms has been disappointing. The introduction of a further stay on mortgage foreclosures sends a highly negative signal about the protection of creditor rights. Continuation of a prudent fiscal policy will be the first challenge for the new administration. A cautious easing of monetary policy appears warranted given recent price and exchange rate trends. The new administration faces enormous challenges in advancing toward an appropriately comprehensive structural reform program.